The Emperor's Qualities and Virtues in the Inscriptions from Augustus to the Beginning of Constantine's Reign: "Mirrors for prince"? : Qualités et vertus de l'empereur dans les inscriptions d'Auguste au début du règne de Constantin: « Miroirs au prince »? - Gangloff, Anne (Classical Studies E-Books Online, Collection 2022., 2022)
This anthology provides valuable new insights into discussions about the virtues, qualities, and position of the emperor in the Roman world (especially with regard to the perception of imperial dominion in the eastern provinces) by systematically focusing on documentary sources, i.e. inscriptions in particular. In addition, the assembled texts contribute to the study of Roman political thought, shaped by earlier traditions primarily during the Principate and the beginning of the Later Roman Empire. Cet ouvrage collectif apporte de nouveaux éclairages précieux aux discussions sur les vertus, les qualités, la position de l'empereur dans le monde romain (notamment sur la perception de la domination impériale dans les provinces orientales), en se concentrant systématiquement sur les sources, c'est-à-dire les inscriptions en particulier. Les textes réunis contribuent également à l'étude de la pensée politique romaine, façonnée par des traditions antérieures, surtout pendant le Principat et le début de l'Antiquité Tardive.